Transgenic and physiological mouse models give insights into different aspects of amyotrophic lateral sclerosis - Francesca De Giorgio; Cheryl Maduro; Elizabeth M. C. Fisher; Abraham Acevedo-Arozena (The Company of Biologists, 2019)
A wide range of genetic mouse models is available to help researchers dissect human disease mechanisms. Each type of model has its own distinctive characteristics arising from the nature of the introduced mutation, as well as from the specific changes to the gene of interest. Here, we review the current range of mouse models with mutations in genes causative for the human neurodegenerative disease amyotrophic lateral sclerosis. We focus on the two main types of available mutants: transgenic mice and those that express mutant genes at physiological levels from gene targeting or from chemical mutagenesis. We compare the phenotypes for genes in which the two classes of model exist, to illustrate what they can teach us about different aspects of the disease, noting that informative models may not necessarily mimic the full trajectory of the human condition. Transgenic models can greatly overexpress mutant or wild-type proteins, giving us insight into protein deposition mechanisms, whereas models expressing mutant genes at physiological levels may develop slowly progressing phenotypes but illustrate early-stage disease processes. Although no mouse models fully recapitulate the human condition, almost all help researchers to understand normal and abnormal biological processes, providing that the individual characteristics of each model type, and how these may affect the interpretation of the data generated from each model, are considered and appreciated.